Papua Special Autonomy and the Relocation Policy of Indigenous Betel Nut Women Vendors in Sorong City: An Interpretative Perspective - Musa Agustinus; Munawar Noor; Sumarmo Sumarmo (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
This study examines the implementation of Papua Special Autonomy in the context of the relocation policy affecting indigenous betel nut vendor women in Sorong City, using an interpretative perspective. The research focuses on how betel nut women vendors understand and experience the relocation policy as indigenous actors directly affected by public policy. The objective of this study is to explore the meanings, experiences, and interpretations constructed by these women in relation to relocation policies under the framework of Papua Special Autonomy.  This research employs a qualitative method with an interpretative approach, utilising in-depth interviews, field observations, and document analysis. The findings reveal that the relocation policy has not fully reflected the core principles of Special Autonomy, particularly in protecting, empowering, and recognising the rights of indigenous Papuans. The women vendors interpret relocation not merely as an urban spatial arrangement, but as a restriction on their economic space and socio-cultural identity.  This study contributes theoretically by enriching the discourse on Special Autonomy from the perspective of local actors, and practically by offering policy recommendations for more inclusive, participatory, and culturally sensitive relocation policies in Papua.